La metodología de ambientes de aprendizaje en educación inicial - Barreno Berreno, Norma Paulina (2017)
This project aims to contribute to the methodology of learning environments and their correct application within the classroom, developing experiences in prepared environments, through play activities in different corners of learning for the development of skills and skills, taking into account the methodology covers this topic within what is the initial education, is thus focused on constructivist theory and based on the method of work, to obtain results technical applications and appropriate instruments that did not provide the necessary facilities in the search for truthful information and objective, such as observation - observation sheet of the survey application and interviews with questionnaires or question bank. Knowing in this way the great impact it causes within the school classrooms and improving the quality of education of direct and indirect beneficiaries, in addition to the opportunity to contribute research is very important and is providing personal support for educational excellence and the application of new methodologies seeking to leave aside the traditional and ambiguous. As the drivers of education are innovative tools such as new methodologies and play as the basis of new learning.